A study of the Islamic influence on traditional Malay Batik Sarongs of Kelantan and Terengganu / Rafeah Legino - Legino, Rafeah (2004)
This research aims to determine the presence of an Islamic influence on the traditional batik sarong of Kelantan and Terengganu. The research is intended to find out if there is any significant Islamic influence in the use of certain structures, dimensions, motifs, principles, and colours in the applied to batik sarongs. Chapter one begins with the introduction, which provides the significance of the study, statement of the problem, delimitation, limitations, research methodology, interview and observation studies of the traditional batik sarong of Kelantan and Terengganu, found in museums as well as in batik-makers' personal collections. Chapter two concentrates on related research and literature pertaining to the definition of batik sarong. It also provides a brief history and a general overview of batik from Kelantan and Terengganu, the applications of the sarong, its designs and Islamic influences. Chapter three describes the theoretical background that relates to the formal analysis of batik sarongs from Kelantan and Terengganu. The Islamic influence is shown in this analysis with detailed drawings and illustrations. This chapter also shows the process of appreciation of batik sarong based on the method designed by Ismail alFaruqi, that is imitation, denaturalization, stylization and abstraction. Chapter four deals with the analysis of the shape and general structure of batik sarongs. The study is based on the research done by Harmen C. Veldhuisen, Abdul Aziz Abdul Rashid, Azah Aziz and the Malaysian Handicraft Development Corporation. The various structures and measurements of the batik sarongs from Kelantan and Terengganu are shown in this chapter. Chapter five explains the term of motif and the identification of the types of motifs used in the batik sarong from Kelantan and Terengganu. It also provides an analysis of the Islamic influences shown in the motifs of every structure to determine the Islamic influence on the samples collected. A brief history of the colours of batik sarong and their significance is discussed in chapter six. The concept of colour and beauty in Islam plays a significant role in the development of the batik sarongs of Kelantan and Terengganu, thus confirming the question of identity in the development of an Islamic aesthetic, as a whole. Chapter seven further describes the general influence of Islam on the development of the art of batik sarong. The influence of Islam can be seen in the motifs and design of batik sarongs from Kelantan and Terengganu. As a conclusion, the study of batik sarongs from Kelantan and Terengganu shows that there is a concrete application and interpretation of Islamic ideas on batik sarongs from Kelantan and Terengganu.